Miles to Go Before I Sleep - Hovitie, Hanna (Finland, 2015)
A story of a nomadic life and a broken identity. As Achat was seven years old, her parents sent her away from Congo to be adopted in France. After her adoptive mother’s death, years of ordinary life in Paris turned into a nightmare. In the film Achat shares her story of becoming a victim of abuse and child trafficking. Through twists and turns beyond belief, she is thrown into a whirlwind of drifting between continents.
Film also on HDD Verzio11/12 located: M22 R17 S2 R4
Verzio Film Festival Submission
Keywords: Documentary films